Calix[n]phenothiazines: Optoelectronic and Structural Properties and Host–Guest Chemistry - Schmidt, Maximilian; Hermann, Mathias; Otteny, Fabian; Esser, Birgit (Organic Materials, 2020)
Calixarenes are of interest as receptors for ions and small molecules and as organic materials. Exchanging the arene units through heteroaromatics allows changing their optoelectronic and host–guest properties. We herein present calix[n]phenothiazines (n = 3, 4) as novel macrocycles, accessible in two-step syntheses. The phenothiazine units show reversible redox events and emissive properties, and N-hexyl-substituted calix[3]phenothiazine binds to both ammonium ions and a bisimidazole as neutral guests.
Keywords: Calixarenes; macrocycles; phenothiazine; host–guest chemistry; conformational flexibility